Akt and cAMP response element binding protein mediate 17β-estradiol regulation of glucose transporter 3 expression in human SH-SY5Y neuroblastoma cell line. (14th September 2015) - Ni, Yaohui; Zhou, Yajun; Zhou, Mingming; Zhang, Luping
Graphical abstract: Highlights: E2 upregulated Glut3 expression in human SH-SY5Y cell line. E2 stimulated the phosphorylation of CREB by Akt pathway. Akt/CREB axis mediated the effect of E2 on Glut3 in human SH-SY5Y cell line. Abstract: Impaired glucose uptake is involved in Alzheimer's disease (AD) and glucose transporter 3 (Glut3) is the major neuronal glucose transporter. Estrogens contribute its theorized protective role against AD. The present studies aimed to examine the effect of 17β-estradiol (E2, the natural estrogen) on Glut3 expression and the underlying mechanisms by using human SH-SY5Y cell line. The results demonstrated that E2 increased Glut3 expression. E2 could stimulate the activation of Akt signaling pathway and the subsequent phosphorylation of cAMP response element binding protein (CREB). Akt/CREB pathway mediated E2-induced increase in Glut3 expression. These results suggested the mechanisms underlying E2-induced increase in Glut3 expression in human SH-SY5Y cell line and might provide the new data for elucidating the neuroprotective role of E2 against AD.